2019
DOI: 10.24085/jsaa.v7i2.3826
|View full text |Cite
|
Sign up to set email alerts
|

Diversity Includes Disability: Experiences of Resilience in a University Residence

Abstract: The provision of residence accommodation is a persistent challenge that is faced by universities across the globe. However, suitable accommodation for students with disabilities is an even greater challenge that is exacerbated by the absence of appropriately designed, maintained and managed residences. In particular, the adverse impact on wheelchair users and students whose disabilities require specific design adaptations is acute. This article will focus on the experiences of students with disabilities in uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…Finally, this review has shown how most studies have exposed the structural inequalities that continue to hamper the participation of students with disability. This trend can be complemented by research that also points the way forward by highlighting examples of how some universities are creating more psychologically safe environments for diversity and enabling inclusive universal design of campuses, welcoming communities, and teaching and learning systems (e.g., Burgstahler, 2021), as well as the related resilience factors that enable students with disability to participate successfully in HE (e.g., Moriña, 2017;Ule, 2017;Duma, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, this review has shown how most studies have exposed the structural inequalities that continue to hamper the participation of students with disability. This trend can be complemented by research that also points the way forward by highlighting examples of how some universities are creating more psychologically safe environments for diversity and enabling inclusive universal design of campuses, welcoming communities, and teaching and learning systems (e.g., Burgstahler, 2021), as well as the related resilience factors that enable students with disability to participate successfully in HE (e.g., Moriña, 2017;Ule, 2017;Duma, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The locations and timing between lectures were a problem for students with visual and physical impairments, leading to late arrival for sessions (Bualar, 2018;Yusof et al, 2020) and tiredness (Mays and Brevetti, 2020). Students listed inaccessible dorms and generally badly designed buildings (Duma, 2019;Francis and Chiu, 2020;García-González et al, 2021), lack of ramps, elevators and automated doors (Braun and Naami, 2021), and inaccessible library areas, and lecturers' offices (Moriña and Morgado, 2018;Mutanga, 2018). According to a Greek study, 'most of the participants talked about unsuitable elevators, stairs and lighting, absence of ramps and of wheelchair accessible toilets as well as classrooms with poor acoustics' (Vlachou and Papananou, 2018, p. 213; see also Yusof et al, 2020).…”
Section: Subtheme 21: Call For Physical Accessibilitymentioning
confidence: 99%
“…Residential stuffs are needed to be trained so that they can understand the resilience and abilities of the SWD. In this case further research is needed on the issue of administrative response and on the difficulty in residential living environment (Duma, 2019). Additionally, more research is needed to provide a better understanding of higher education institutions' barriers and facilitators to success, as the current literature is limited.…”
Section: Introductionmentioning
confidence: 99%